Integrating Science and Religion: Tadris Biology Students' Perspectives on the Covid-19 Pandemic - Warda Hayya, Adieba; Fadla, Nilna (Journal of Educational Integration and Development (JEID), 2025)
The Covid-19 pandemic has challenged individuals to reconcile scientific knowledge with religious beliefs, particularly among Tadris Biology students. This study explores their perspectives on integrating science and religion in understanding the pandemic through a mixed-methods approach. Quantitative surveys assessed students’ knowledge and attitudes, while qualitative interviews, focus group discussions (FGDs), and document analysis provided deeper insights. Findings indicate that students generally understand Covid-19, vaccines, and the role of science in pandemic mitigation, though some misconceptions persist. Religiously, they acknowledge prayer and worship as vital coping mechanisms while considering scientific preventive measures as part of their faith-driven efforts. Statistical analysis using SPSS and thematic analysis of qualitative data highlight key themes such as faith-based coping, scientific misconceptions, and perceived harmony between science and religion. This study underscores the necessity of integrating science and religion in Tadris Biology education to promote a holistic understanding of pandemics and public health. The interdisciplinary approach enhances curriculum adaptability to global challenges, fostering a balanced and informed perspective among students. The findings suggest that blending scientific and religious views can provide a comprehensive framework for addressing contemporary issues in education and public health.